1994
DOI: 10.1111/j.1365-2958.1994.tb00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and primary structure of Staphylococcus aureus DNA topoisomerase IV: a primary target of fluoroquinolones

Abstract: A 4.6 kb Staphylococcus aureus DNA fragment containing DNA gyrase-like genes (grlA and grlB) was cloned and sequenced. The proteins GrlA and GrlB exhibit more than 30% identity with E. coli DNA topoisomerase IV subunits and with the gyrase subunits from S. aureus and Escherichia coli. The combined E. coli cell extracts of GrlA and GrlB overproducing strains catalysed ATP-dependent relaxation and decatenation specific to DNA topoisomerase IV. The temperature-sensitive phenotype of Salmonella typhimurium parC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
329
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(349 citation statements)
references
References 41 publications
18
329
0
1
Order By: Relevance
“…The detection of a mutation in the ParC QRDR suggests that the parC gene might be the primary target of enrofloxacin in M. synoviae as described for M. bovirhinis [16] or Staphylococcus aureus (grlA) [11]. Previous studies have shown Topoisomerase IV to be the primary target of ciprofloxacin (analogous to enrofloxacin) in M. hominis [3].…”
Section: Discussionmentioning
confidence: 99%
“…The detection of a mutation in the ParC QRDR suggests that the parC gene might be the primary target of enrofloxacin in M. synoviae as described for M. bovirhinis [16] or Staphylococcus aureus (grlA) [11]. Previous studies have shown Topoisomerase IV to be the primary target of ciprofloxacin (analogous to enrofloxacin) in M. hominis [3].…”
Section: Discussionmentioning
confidence: 99%
“…In S pneumoniae, low-level fluoroquinolone resistance to ciprofloxacin and levofloxacin has been associated with mutations in the QRDR of parC. However, high-level resistance requires additional mutations in the QRDR of gyrA (255)(256)(257)(258)(259). Decreased accumulation: Acquired fluoroquinolone resistance due to active efflux in S pneumoniae has been shown to be due to increased levels of expression of efflux pumps mediated by the pmrA gene (260).…”
Section: Fluoroquinolone Resistancementioning
confidence: 99%
“…Amino acid replacement correlating with fluoroquinolone resistance in GrlA include Ser80->Phe or Tyr, Ala116->Glu or Pro, and Glu84->Lys (Kaatz & Seo, 1997;Agents an chemotherapy, 1992;Ferrero et al, 1994;Ferrero et al, 1995;Yamagishi et al, 1996). With respect to GyrA, Ser84->Leu or Ala, Ser85->Pro and Glu88->Lys mutations are associated with fluoroquinolone resistance (Kaatz & Seo, 1997;Goswitz et al, 1992;Kaatz & Seo, 1995) amino acid replacement in GyrB correlating with fluoroquinolone resistance include Asp437->Asn and Arg458->Glu (Ito et al, 1994;Kaatz & Seo, 1997).…”
Section: Introductionmentioning
confidence: 99%